Mathematical Language of Students with Learning Disabilities in the Context of Length - Güven, Dilsad; Argün, Ziya (Athens Journal of Education, 2022)
Mathematics is language dependent. Part of learning mathematics is learning the mathematical language. Learning disabilities are defined as disorders that are related to listening, thinking, speaking, writing, and reading that are seen in the processes of understanding or using a verbal or written language. In this context, the present study aimed to reveal the understanding and usage of the mathematical language of students with learning disabilities in the context of the concept of length. This study was conducted as a case study. The participants of the study were 4th grade and 5th grade students with learning disabilities. Data collection was conducted through semi-structured clinical interviews during a teaching experiment based on the concept of length and analysed using the content analysis method. According to the findings, the students with learning disabilities had a different and limited understanding, as well as usage of various mathematical terms including length, height, perimeter, half and centimetre. Keywords: mathematical language, learning disabilities, length concept, mathematics education, special education